Consulting doctors online after offline treatment: investigating the effects of online information on patients' effective use of online follow-up services - Han, Shuhui; Li, Lun (Frontiers in Public Health, 2024)
The use of oOnline follow-up services (OFUS) are is increasingly becoming an increasingly important supplements to hospital care.s, Through OFUS, which enables patients can to find the correspondingtheir doctors in online health communities (OHCs) for and receive remote medical follow-ups after hospital they receive treatment in hospitals. However, the rate of effective use of OFUS by current patients is still low,. Thereforeand there is an urgent need for research, to investigateing the online information factors that affect patients' effective use of OFUS becomes largely important. Based on the elaboration likelihood model (ELM) of persuasion and an analysis of a panel dataset including 3,672 doctors in a leading OHC in China, this study seeks to explores the effects ofhow online information about from doctors' knowledge contributions and patient feedback influences on patients' effective use of OFUS.With an analysis of a panel dataset including 3,672 doctors from a leading OHC in China, Tthe results show that both doctors' knowledge contributions and patient feedback have positively effects oninfluence persuading patients' effective use of OFUS. Specifically, dDoctors' paid knowledge contributions and (patients' paid feedback) haves a stronger persuasive effects than doctors' free knowledge contributions and patients' (free feedback, respectively). Moreover, there is also a substitutional relationship in influencing patients' effective use of OFUS between doctors' paid knowledge contribution and free knowledge contributions and (between patients' paid feedback and free feedback in influencing patients' effective use of OFUS). The findings of this study suggest that OHC platforms and healthcare providers should account for not only for the persuasive effects of doctors' knowledge contributions and patient feedback but also for influentialcing differences and relationships between the different types of doctors' knowledge contributions and (patient feedback), which is helpful to better persuade patients to effectively use OFUS.